Thematic Review of Endocrine Disruptors and Their Role in Shaping Pubertal Timing - And Demir; Adem Aydin; Atilla Büyükgebiz (Children)
This review examines the inconsistent effects of endocrine-disrupting chemicals (EDCs) and pollutants on pubertal timing, emphasizing the methodological challenges contributing to variability in findings. Data from nine key studies reveal that chemicals such as BPA, phthalates, and PFAS impact pubertal onset differently based on exposure timing, dosage, and sex. For instance, BPA is linked to earlier puberty in girls but delayed onset in boys, while other EDCs show mixed effects across populations. These discrepancies often arise from challenges in study design, such as the difficulty in establishing reliable control groups, accurately measuring exposures, and accounting for confounding factors like socioeconomic status, diet, and obesity. Sex-specific differences and environmental shifts during the COVID-19 pandemic, including increased indoor exposure and stress, further complicate the picture. These factors highlight the urgent need for more robust research methodologies, including standardized exposure assessments and longitudinal studies, to clarify the mechanisms driving these effects. Despite these challenges, the findings stress the importance of public health interventions, such as stricter EDC regulations, improved pollutant monitoring, and minimizing exposures during sensitive developmental windows. Addressing methodological gaps is crucial for producing reliable, actionable insights to protect adolescent development from the adverse effects of EDCs.